2007
DOI: 10.1093/jac/dkm024
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic resistance in Campylobacter jejuni and Campylobacter coli isolated from poultry in the South-East Queensland region

Abstract: This work has shown that the majority of C. jejuni and C. coli isolates were susceptible to the six antibiotics tested by both disc diffusion and MIC methods. Disc diffusion represents a suitable alternative methodology to agar-based MIC methods for poultry Campylobacter isolates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
54
0
2

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(62 citation statements)
references
References 15 publications
6
54
0
2
Order By: Relevance
“…Sensitivity to chloramphenicol by all Campylobacter isolates was also observed by Sáenz et al (2000) and Guévremont et al (2006) in pigs, whereas Bardon et al (2009) andMiflin et al (2007) found similar resistance patterns for Campylobacter spp. obtained from humans and chickens, respectively.…”
Section: Discussionsupporting
confidence: 72%
See 2 more Smart Citations
“…Sensitivity to chloramphenicol by all Campylobacter isolates was also observed by Sáenz et al (2000) and Guévremont et al (2006) in pigs, whereas Bardon et al (2009) andMiflin et al (2007) found similar resistance patterns for Campylobacter spp. obtained from humans and chickens, respectively.…”
Section: Discussionsupporting
confidence: 72%
“…On the other hand, Miflin et al (2007) found sensitivity to ciprofloxacin for all the 152 strains of Campylobacter spp. isolated from chicken in Australia, whereas Inglis et al (2005) confirmed ciprofloxacin resistance in only 0.3% of isolates from cattle in Canada.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…The flagellin gene has been a well-accepted marker for Campylobacter genotyping for over 2 decades (4,16,18,19,22,25,32). In this study we have developed a genotyping method based on flaA interrogation using HRM analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Antimicrobial discs (Oxoid, Basingstoke, UK) were placed on the inoculated MHB plates and they were incubated in the VAIN for 48 h. The following antimicrobial discs were used: aztreonam, tetracycline, gentamicin, cephalothin, amoxicillin-clavulanic acid, nalidixic acid, chloramphenicol, erythromycin (all 30 µg), streptomycin (25 µg), and ciprofloxacin (5 µg). Interpretation of the results was performed using the resistance breakpoint for Campylobacters described by others [14,15]. When no breakpoints were available for Campylobacters, the resistance breakpoint described by CLSI for Enterobacteriaceae was used.…”
Section: Antibiotic Susceptibility Testingmentioning
confidence: 99%